The Making of the University of the Philippines Anthropology Field School 2022 - Cagurangan, Joulianna Ysabel C.; Cordero, Doms; Dorosan, Marvin D.; Pauchano, Bryan; Santiago, Franchesca Emery M. (anthropozine: The Official Publication of the University of the Philippines H. Otley Beyer Museum of Anthropology, 2025)
Drawing on the researchers’ unique positionality as participants of the field school, the paper is a result of a process of conversation, insight-building, theoretical plotting, and data analysis done in the course of the field school’s face-to-face and online components.